Regulation of sodium channel densities in A6 renal epithelial cells by hormonally-dependent mechanisms - Butterworth, Michael Bruce (Department of Human Biology, 2023)
Epithelial sodium channels (ENaC) located in the apical membranes of transporting epithelia, such as cells of the renal distal nephron, constitute the rate limiting step in the transcellular transport of sodium. The regulation of sodium ion reabsorption in the kidney, which is essential for salt and water homeostasis, is therefore governed by the cellular control of ENaC activity. It is well established that the neurohypophysial hormone vasopressin (antidiuretic hormone) is responsible for both water and sodium regulation and, in renal cells, increases sodium permeability by regulating ENaCs at their apical membranes. The mechanisms involved in acute ENaC regulation have however not been demonstrated unequivocally. Evidence exists to suggest that sodium ion transport rates could be increased either by direct activation of membrane-resident ENaCs, or recruitment of channels from cytoplasmic storage pools. In order to address the issue, this study aimed to investigate the hypothesis that vasopressin regulation of ENaC occurred by targeted exocytic delivery of channels to the apical membrane from sub-apical pools. All investigations were carried out on the sodium transporting A6 cultured cell line derived from Xenopus laevis kidney. The secondary messenger pathway of vasopressin stimulation had not been extensively characterised in these cells and this was the first study undertaken. Once it was established that an adenosine-3',5'-cyclic monophosphate (cAMP) secondary messenger pathway was in operation, attention was shifted to ENaC regulation in response to a raised intracellular cAMP level. The electrophysiological technique of current-fluctuation analysis was employed to characterise the single channel response to cAMP production. These studies demonstrated that the main factor responsible for increased sodium transport was a dramatic increase in the number of channels at the apical surface despite declines in both single channel conductance and channel open probability. Investigating intracellular membrane traffic by marker-uptake and confocal microscopic techniques demonstrated that cAMP pre-stimulation significantly altered the rates of membrane endocytosis from the apical surface implicating regulated recruitment and retrieval mechanisms for ENaC regulation. These methods provided indirect evidence for the shuttling hypothesis and established that the vesicle trafficking machinery was responsive to cAMP, but did not associate ENaC directly with the process. In order to demonstrate the movement of ENaC in conjunction with membrane trafficking mechanisms, a green fluorescent protein (GFP) tagged-ENaC was employed. By using live cell confocal microscopic techniques, the dynamic movement of GFP-ENaC in response to cAMP was demonstrated. Shuttling of ENaC to the apical surface was observed on cAMP stimulation with endocytic retrieval on removal of stimulus. For the first time in live cells these data directly demonstrate the dynamic regulation of ENaC by shuttling mechanisms.